Multi-Material Wire Arc Additive Manufacturing of low and high alloyed aluminium alloys with in-situ material analysis. (September 2021) - Hauser, Tobias; Reisch, Raven T.; Seebauer, Stefan; Parasar, Aashirwad; Kamps, Tobias; Casati, Riccardo; Volpp, Joerg; Kaplan, Alexander F.H.
Abstract: In recent years, the interest in the improved functionalisation of Additive Manufacturing components through multi-material solutions has increased because of the new possibilities in product design. In this work, an advanced Wire Arc Additive Manufacturing process for fabrication of multi-material structures of different aluminium alloys was investigated. Mechanical properties such as tensile strength, yield strength, fracture elongation, and hardness were analysed for multi-material parts and compared with the mechanical properties of mono-material parts. It was found that the strength of multi-material components was limited by the properties of the individual aluminium alloys and not by those of the material transition zones. Microsections and EDX line scans revealed a smooth transition zone without any significant defects. Furthermore, process monitoring approaches for quality assurance of the correct material composition in such multi-material structures were investigated. Different sensor data were captured during multi-material Wire Arc Additive Manufacturing to identify and observe various characteristics of the process. It was shown that the voltage, current, acoustic, and spectral emission data can be used for in-situ monitoring to detect the chemical differences between the two aluminium alloys 6060 and 5087. Characteristic patterns in the frequency range were found, which can be attributed to a frequency shift that occurred due to the different material properties. Spectral analysis revealed changes in the ratios of green and blue light emission to red light emission, which was also due to the different magnesium contents.